2016
DOI: 10.1002/anie.201511354
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Neutron Diffraction to Probe Local Magnetic Anisotropy of a Low‐Spin Fe(III) Complex

Abstract: We have determined by polarized neutron diffraction (PND) the low‐temperature molecular magnetic susceptibility tensor of the anisotropic low‐spin complex PPh4[FeIII(Tp)(CN)3]⋅H2O. We found the existence of a pronounced molecular easy magnetization axis, almost parallel to the C3 pseudo‐axis of the molecule, which also corresponds to a trigonal elongation direction of the octahedral coordination sphere of the FeIII ion. The PND results are coherent with electron paramagnetic resonance (EPR) spectroscopy, magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…The main difficulty with these methods is to access the local magnetic anisotropy even when performed on single crystals. We recently showed that polarized neutron diffraction (PND) provides a unique tool to establish precise magneto-structural relationships in mononuclear and dinuclear transition metal complexes of Fe 3+ and Co 2+ ions [9,10]. In this paper we report the study, by angular-resolved magnetometry and polarized neutron diffraction, of the magnetic anisotropy of the [Ni4(L)4(MeOH)4] cluster (Figure 1), so-called [Ni4].…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulty with these methods is to access the local magnetic anisotropy even when performed on single crystals. We recently showed that polarized neutron diffraction (PND) provides a unique tool to establish precise magneto-structural relationships in mononuclear and dinuclear transition metal complexes of Fe 3+ and Co 2+ ions [9,10]. In this paper we report the study, by angular-resolved magnetometry and polarized neutron diffraction, of the magnetic anisotropy of the [Ni4(L)4(MeOH)4] cluster (Figure 1), so-called [Ni4].…”
Section: Introductionmentioning
confidence: 99%
“…[55] In this case, the spin-orbit coupling is treated variationally within the two-component spin-orbit ZORA formalism. The introduction of spin polarization into the g-factor calculations has been tested in previous work [14] and did not converge to the correct ground state (see Ta ble S13 in the Supporting Information). The introduction of spin polarization into the g-factor calculations has been tested in previous work [14] and did not converge to the correct ground state (see Ta ble S13 in the Supporting Information).…”
Section: Computational Detailsmentioning
confidence: 99%
“…[8] Here, the versatility of the scorpionate ligandsp ermits the adjustment of the steric ande lectronic properties of the precur-sor,a nd hence allows tuning the magnetic properties. [14] In the present work, we have continued to exploret echniques that allow magnetic properties to be probeda tt he local scale. [9][10][11][12][13] Af ew years ago, we undertook af undamental study of the [Fe III (Tp)(CN) 3 ] À building block with the aim of gaining a deeper understanding of its properties by probing the magnetism at the local level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations